Echo and natriuretic peptide guided therapy improves outcome and reduces worsening renal function in systolic heart failure: An observational study of 1137 outpatients. (1st December 2016) - Simioniuc, Anca; Carluccio, Erberto; Ghio, Stefano; Rossi, Andrea; Biagioli, Paolo; Reboldi, Gianpaolo; Galeotti, Gian Giacomo; Lu, Fei; Zara, Cornelia; Whalley, Gillian; Temporelli, Pier Luigi; Dini, Frank Lloyd; et al.
Abstract: Background: B-type natriuretic peptide (BNP) and echocardiography are potentially useful adjunct to guide management of patients with chronic heart failure (HF).Thus, the aim of this retrospective, multicenter study was to compare outcomes and renal function in outpatients with chronic HF with reduced ejection fraction (HFrEF) who underwent an echo and BNP guided or a clinically driven protocol for follow-up. Methods and results: In 1137 consecutive outpatients, management was guided according to echo-Doppler signs of elevated left ventricular filling pressure and BNP levels conforming to the protocol of the Network Labs Ultrasound (NEBULA) in HF Study Group in 570 (mean EF = 30%), while management was clinically driven based on the institutional protocol of the HF Unit of the Cardiovascular and Thoracic Department in 567 (mean EF = 33%). Propensity score, matching several confounding baseline variables, was used to match pairs based on treatment strategy. The median follow-up was 37.4 months. After propensity matching, a lower incidence of death (HR 0.45, 95%CI: 0.30–0.67, p < 0.0001), and death or worsening renal function (HR 0.49, 95%CI 0.36–0.67, p < 0.0001) was apparent in echo-BNP-guided group compared to clinically-guided group. Worsening of renal function (≥ 0.3 mg/dl increase in serum creatinine) was observed in 9.8% of echo-BNP-guided group and in 21.4% of clinical assessed group ( p < 0.0001). The daily dose of loop diuretics did not change in echo-BNP-guided group, while it increased in 65% of patients in clinically-guided group ( p < 0.0001). Conclusions: Echo and BNP guided management may improve the outcome and reduce worsening of renal function in outpatients with chronic HFrEF.